IMPLEMENTASI MATA KULIAH MANAJEMEN PROYEK DALAM BENTUK PELAKSANAAN PROYEK MINI - Slamet, Kuwat (Polytechnic of State Finance STAN, 2016)
Is it needed to assign vocational education students group work in the form of mini project to implement a project management course material? To answer these questions, the author conducted an analysis of the implementation of mini project undertaken by class 5E and 5G students of Diploma III Program of State Treasury in PKN STAN. Students were divided into 10 groups and were given a four-week-deadline to complete the project. Through this activity, students are faced with an actual description of the process of planning, implementation, evaluation, and reporting of an activity. The authors conclude that this assignment provides positive advantages to students. They acquire a broad understanding of how the management of a real project works and any obstacles encountered on the completion of a project. Analysis of the implementation of these activities can also provide input to PKN STAN and other vocational education management in designing curricula more precisely.